Lichen Biomonitoring of Airborne Microplastics in Milan (N Italy) - Mehriban Jafarova; Tania Contardo; Julian Aherne; Stefano Loppi (Biology, 2022)
This study investigated the deposition of airborne microplastics (MPs) in the urban area of Milan across 12 sites and at a background control site (northern Italy) using 3-month transplants of the fruticose lichen species Evernia prunastri (exposed in triplicate). The primary objective was to evaluate the use of lichen transplants for the assessment of MP deposition; as such, the study sites spanned a gradient in vehicular traffic and population density across four concentric land-use zones (i.e., urban parks, centre, semi-periphery, and periphery). A total of 149 MP particles were detected in the exposed lichen samples; 94.6% were classified as fibres and 5.4% as fragments. The control site and urban parks experienced a similar number of MPs per gram of dry lichen (20–26 MP/g), while a higher number of MPs were detected in central and peripheral areas (44–56 MP/g), with a clear increasing gradient from the city centre towards the periphery. We estimated the MP deposition in Milan to be in the range of 43–119 MPs m2/d, indicating that people living in Milan are exposed to airborne MPs, with potential health effects. This study suggests that lichens are suitable biomonitors of airborne MPs under a relatively short exposure of three months in urban environments.